Poly(ethylene glycol) diacrylate/hyaluronic acid semi-interpenetrating network compositions for 3-D cell spreading and migration. (1st March 2015) - Lee, Ho-Joon; Sen, Atanu; Bae, Sooneon; Lee, Jeoung Soo; Webb, Ken
Graphical abstract: Abstract: To serve as artificial matrices for therapeutic cell transplantation, synthetic hydrogels must incorporate mechanisms enabling localized, cell-mediated degradation that allows cell spreading and migration. Previously, we have shown that hybrid semi-interpenetrating polymer networks (semi-IPNs) composed of hydrolytically degradable poly(ethylene glycol) diacrylates (PEGdA), acrylate-PEG-GRGDS and native hyaluronic acid (HA) support increased cell spreading relative to fully synthetic networks that is dependent on cellular hyaluronidase activity. This study systematically investigated the effects of PEGdA/HA semi-IPN network composition on 3-D spreading of encapsulated fibroblasts, the underlying changes in gel structure responsible for this activity, and the ability of optimized gel formulations to support long-term cell survival and migration. Fibroblast spreading exhibited a biphasic response to HA concentration, required a minimum HA molecular weight, decreased with increasing PEGdA concentration and was independent of hydrolytic degradation at early time points. Increased gel turbidity was observed in semi-IPNs, but not in copolymerized hydrogels containing methacrylated HA, which did not support cell spreading. This suggests that there is an underlying mechanism of polymerization-induced phase separation that results in HA-enriched defects within the network structure. PEGdA/HA semi-IPNs were also able to support cell spreading at relatively high levels of mechanical properties (∼10 kPa elastic modulus) compared to alternative hybrid hydrogels. In order to support long-term cellular remodeling, the degradation rate of the PEGdA component was optimized by preparing blends of three different PEGdA macromers with varying susceptibility to hydrolytic degradation. Optimized semi-IPN formulations supported long-term survival of encapsulated fibroblasts and sustained migration in a gel-within-gel encapsulation model. These results demonstrate that PEGdA/HA semi-IPNs provide dynamic microenvironments that can support 3-D cell survival, spreading and migration for a variety of cell therapy applications.